2002
DOI: 10.1046/j.1365-2036.16.s4.3.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mild to moderate ulcerative colitis and pouchitis

Abstract: SUMMARYThe meta-analyses of published trials have shown topical therapy with 5-aminosalicylic acid (5-ASA) to be the treatment of choice in active distal ulcerative colitis. Oral aminosalicylates are effective for both distal and extensive ulcerative colitis, but in distal colitis the rates of improvement and remission are usually lower than those reported for rectal 5-ASA therapy. An alternative to 5-ASA therapy is represented by the new steroids; budesonide and beclometasone dipropionate (BDP) enemas, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 56 publications
0
35
0
4
Order By: Relevance
“…However, in patients with proctitis or left sided colitis topical application of 5-ASA as suppository, enema or foam preparation is more effective as compared to systemic treatment. 2 Topically administrated steroids are superior to placebo in this situation, however, inferior if compared to topical 5-ASA. 3,4 Therefore the treatment of choice in mild to moderate left-sided colitis is 5-ASA foams or enemas.…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with proctitis or left sided colitis topical application of 5-ASA as suppository, enema or foam preparation is more effective as compared to systemic treatment. 2 Topically administrated steroids are superior to placebo in this situation, however, inferior if compared to topical 5-ASA. 3,4 Therefore the treatment of choice in mild to moderate left-sided colitis is 5-ASA foams or enemas.…”
Section: Introductionmentioning
confidence: 99%
“…51 Several studies imply further that combinations of different strains of probiotic bacteria are more effective than single-strain preparations. [52][53][54] However, little is known about the optimal mixture in the treatment of different intestinal disorders. Even though animal studies have shown promising results using probiotics in acute inflammatory disorders, the outcomes in human studies with similar settings have not been equally successful.…”
Section: Discussionmentioning
confidence: 99%
“…Una mezcla de varias cepas probióticas ha mostrado que ejerce efectos beneficiosos en el tratamiento de la colitis ulcerosa leve (64)(65)(66), en el tratamiento de la reservoritis y el mantenimiento de la remisión (67,68). Los estudios de pacientes con reservoritis en remisión mediante PCR en tiempo real han mostrado que el VSL#3 aumenta el número total de células bacterianas (p = 0,002) y modifica el espectro de bacterias en favor de las especies anaeróbicas.…”
Section: Probióticos Prebióticos Simbióticos Alimentos Nuevos O Nounclassified